A coated modified graphite negative electrode material and its preparation method and application

By covering the graphite surface with sodium saccharin, the lithium ion transmission and charge and discharge performance problems of graphite negative electrode materials in sulfide solid-state batteries are solved, and more stable and efficient battery performance is achieved.

CN118676339BActive Publication Date: 2025-04-22GAO NENG SHI DAI (SHEN ZHEN) XIN NENG YUAN KE JI YOU XIAN GONG SI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410821345.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-24
Publication Date
2025-04-22
Estimated Expiration
2044-06-24

AI Technical Summary

Technical Problem

As the negative electrode material of sulfide solid-state battery, graphite has long lithium ion transmission path, limited charging rate and capacity performance, easy formation of lithium dendrites, resulting in battery short circuit and safety problems.

Method used

By covering the surface of the graphite, the contact area between the graphite and the electrolyte is increased, the lithium ion conductivity is improved, and the lithium metal deposition is regulated through the saccharin sodium, and the formation of lithium dendrites is inhibited.

Benefits of technology

It improves the charging and discharging performance of sulfide solid-state batteries, slows down the rapid attenuation of capacity at large-scales, and improves the safety and stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118676339B_ABST
    Figure CN118676339B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of battery technology, and discloses a coated modified graphite negative electrode material, a preparation method and an application thereof. The coated modified graphite negative electrode material of the present invention comprises graphite and sodium saccharin, and the sodium saccharin is coated on at least part of the surface of the graphite. The coated modified graphite negative electrode material provided by the present invention, in which sodium saccharin is coated on the surface of graphite, can increase the contact area between graphite and electrolyte, and improve the lithium ion conductivity; at the same time, sodium saccharin regulates lithium metal deposition, inhibits the formation of lithium dendrites during charging and discharging, prevents battery short circuit from causing safety problems, and slows down the sharp drop in battery capacity; the coated modified graphite negative electrode material of the present invention has a stable electrode interface, which can slow down the rapid attenuation of the capacity of sulfide solid-state batteries at high rates, thereby improving the charge and discharge performance of sulfide solid-state batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries, and in particular relates to a coated modified graphite negative electrode material and a preparation method and application thereof. Background Art

[0002] As an important electrochemical energy storage device, lithium-ion batteries have been widely used in portable electronic devices such as mobile phones and laptops, as well as electric vehicles, due to their advantages such as high energy density, long cycle stability and low self-discharge rate. Electrode materials are the decisive factors in the electrochemical properties of lithium-ion batteries. Graphite has been widely used due to its advantages such as good conductivity, stable structure and low cost, but it still faces huge challenges as anode material for sulfide solid-state batteries. The layered structure of graphite leads to a long lithium ion transmission path, which is not conducive to lithium ion diffusion; the charging rate and capacity of graphite as the negative electrode of sulfide solid-state batteries are greatly limited at higher rates; sulfide solid-state batteries are prone to form lithium dendrites during the charging and discharging process, which can easily cause battery short circuits and safety problems. Summary of the invention

[0003] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a coated modified graphite negative electrode material and a preparation method and application thereof, wherein the coated modified graphite negative electrode material can increase the contact area between graphite and electrolyte, improve lithium ion conductivity, inhibit the formation of lithium dendrites, slow down the rapid capacity decay of sulfide solid-state batteries at high rates, and effectively improve the charge and discharge performance of sulfide solid-state batteries.

[0004] In a first aspect, the present invention provides a coated modified graphite negative electrode material, wherein the coated modified graphite negative electrode material comprises graphite and sodium saccharin, wherein the sodium saccharin is coated on at least a portion of the surface of the graphite.

[0005] The inventive concept of the present invention is that the challenges currently faced by graphite negative electrodes are mainly low specific capacity and relatively low discharge specific capacity; the graphite layered structure limits the diffusion rate of lithium ions, limits the capacity, and is prone to form lithium dendrites during the charge and discharge process, which is easy to cause the risk of battery short circuit and greatly reduce the battery life; and doping and coating are a mainstream means of modifying graphite. After modification, the structure and surface state of the graphite negative electrode during the cycle can be protected, and the stability of the charge and discharge performance can be improved. Based on this, the present invention coats saccharin sodium on the surface of graphite particles, which can increase the contact area between graphite and electrolyte and improve lithium ion conductivity; because the dissociated anions of saccharin sodium have different coordination positions at the metal center, saccharin sodium blocks specific surface sites by forming ion complexes, ion pairing and interacting with substrates, thereby affecting the ion deposition process. In the metal deposition process, saccharin sodium can guide the uniform deposition of metal ions, making the deposition product smooth, fine-grained and dense in morphology. The present invention regulates lithium metal deposition by introducing sodium saccharin, inhibits the formation of lithium dendrites during charging and discharging, prevents battery short circuit from causing safety problems, and slows down the sharp drop in battery capacity. The coated modified graphite negative electrode material of the present invention has a more stable surface state than a conventional single graphite negative electrode, can slow down the rapid attenuation of the capacity of sulfide solid-state batteries at high rates, fully utilizes the capacity of active materials, and effectively improves the charging and discharging performance of sulfide solid-state batteries.

[0006] In some embodiments of the present invention, the mass of the saccharin sodium accounts for 0.1-1% of the mass of the coated modified graphite negative electrode material, for example, it can be any point value among 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, or a range value between any two point values.

[0007] In some embodiments of the present invention, the graphite includes natural graphite and / or artificial graphite, preferably artificial graphite.

[0008] In some embodiments of the present invention, the particle size of the graphite is 5 to 30 μm.

[0009] In some embodiments of the present invention, the purity of saccharin sodium is ≥98%.

[0010] The second aspect of the present invention provides a method for preparing the coated modified graphite negative electrode material according to the first aspect of the present invention, comprising the following steps:

[0011] Mixing graphite, sodium saccharin and solvent, and performing ultrasonic dispersion to obtain a dispersion;

[0012] The dispersion is centrifuged to collect the solid phase, and then the solid phase is dried and sintered to obtain a coated modified graphite negative electrode material.

[0013] In some embodiments of the present invention, the solvent comprises at least one of water, ethanol and propanol, preferably water.

[0014] In some embodiments of the present invention, the ultrasonic dispersion process includes: firstly mixing graphite and a solvent, and then ultrasonically dispersing the mixture, and then adding sodium saccharin and continuing to ultrasonically disperse the mixture.

[0015] In some embodiments of the present invention, the ultrasonic dispersion time is 10 to 60 min; and / or the ultrasonic dispersion frequency is 30-60 kHz.

[0016] In some embodiments of the present invention, before centrifugation, the dispersion is further stirred at a speed of 500 to 1500 rpm, preferably 1000 rpm; and / or the stirring time is 6 to 12 h, preferably 12 h.

[0017] In some embodiments of the present invention, the drying temperature is 50-80° C., preferably 60° C.; and / or the drying time is 6-12 h, preferably 12 h.

[0018] In some embodiments of the present invention, the sintering process includes: heating to 100-300°C at a heating rate of 8-12°C / min under an inert gas atmosphere, and keeping the temperature for 2-4 hours. Preferably, the inert gas is nitrogen, the heating rate is 10°C / min, the temperature is raised to 200°C, and the temperature is kept for 3 hours.

[0019] According to a third aspect of the present invention, a solid-state battery is provided, wherein the solid-state battery comprises the coated modified graphite negative electrode material according to the first aspect of the present invention.

[0020] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0021] The coated modified graphite negative electrode material provided by the present invention has sodium saccharinate coated on the surface of graphite, which can increase the contact area between graphite and electrolyte and improve lithium ion conductivity; at the same time, sodium saccharinate regulates lithium metal deposition, inhibits the formation of lithium dendrites during charging and discharging, prevents safety problems caused by battery short circuit, and slows down the sharp drop in battery capacity; the coated modified graphite negative electrode material of the present invention has a stable electrode interface, can slow down the rapid attenuation of the capacity of the sulfide solid-state battery at a high rate, thereby improving the charging and discharging performance of the sulfide solid-state battery.

[0022] The sodium saccharin coated graphite negative electrode material provided by the present invention is of great significance for realizing safe and high-rate performance sulfide solid-state batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1This is a SEM image of the coated modified graphite negative electrode material obtained in Example 1;

[0024] Figure 2 This is a mapping diagram of the carbon element of the coated modified graphite negative electrode material obtained in Example 1;

[0025] Figure 3 This is a mapping diagram of sulfur element in the coated modified graphite negative electrode material obtained in Example 1;

[0026] Figure 4 This is a first cycle charge and discharge curve diagram of the sulfide solid-state battery obtained in Example 1;

[0027] Figure 5 This is a diagram of the discharge specific capacity of the sulfide solid-state battery obtained in Example 1 at different rates. DETAILED DESCRIPTION

[0028] The present invention is further described in detail below by specific examples. The raw materials, reagents or devices used in the examples can be obtained from conventional commercial sources or by prior art methods unless otherwise specified. Unless otherwise specified, the experiments or test methods are conventional methods in the art.

[0029] Example 1: Preparation of coated modified graphite negative electrode material and solid-state battery

[0030] A method for preparing a coated modified graphite negative electrode material comprises the following steps:

[0031] (1) 9.95 g of artificial graphite (particle size 15 μm) was weighed and placed in 60 mL of deionized water. Ultrasonic dispersion was performed at an ultrasonic frequency of 40 kHz for 20 min. Then, 0.05 g of saccharin sodium (purity 98%) was added and ultrasonic dispersion was continued for 20 min to obtain a dispersion;

[0032] (2) The dispersion obtained in step (1) was magnetically stirred at 1000 rpm for 12 h at 25° C., and then centrifuged three times at 8000 rpm to collect the solid phase;

[0033] (3) After the solid phase obtained in step (2) is dried at 60° C. for 12 h, it is placed in a crucible, and the temperature is increased to 200° C. at a rate of 10° C. / min in a tubular furnace under a nitrogen atmosphere, and kept warm for 3 h to obtain a coated modified graphite negative electrode material.

[0034] A method for preparing a sulfide solid-state battery comprises the following steps:

[0035] (1) 0.3 g of the coated modified graphite negative electrode material obtained above was used as the active material, and the active material was placed in a mortar, and 0.2 g of sulfide electrolyte (LiP) was added to the mortar.6 S 5 Cl) and 0.05g of conductive agent nanocarbon fiber (VGCF), mixed and ground for 10min, then added 0.05g of binder polytetrafluoroethylene (PTFE) and ground for 10min, rolled into a sheet, and cut into a circular electrode with a diameter of 8mm to obtain a negative electrode sheet;

[0036] (2) Place the negative electrode obtained in step (1) into a mold and add LiP 6 S 5 Cl, Li-In alloy is used as the counter electrode and pressed at a pressure of 450MPa to obtain a sulfide solid-state battery.

[0037] The coated modified graphite negative electrode material prepared in Example 1 was observed using a scanning electron microscope (SEM), and the SEM image thereof is as follows: Figure 1 As shown, the element distribution measurement (Mapping) of the coated modified graphite negative electrode material prepared in Example 1 is performed, and the mapping diagrams of the carbon element and the sulfur element are respectively Figure 2 and Figure 3 As shown, comprehensive Figures 1 to 3 It can be seen that the sulfur element in sodium saccharin is attached to the graphite particles, that is, sodium saccharin is coated on the surface of the graphite particles.

[0038] Example 2: Preparation of coated modified graphite negative electrode material and solid-state battery

[0039] A method for preparing a coated modified graphite negative electrode material comprises the following steps:

[0040] (1) 9.95 g of artificial graphite (particle size 15 μm) was weighed and placed in 60 mL of deionized water. Ultrasonic dispersion was performed at an ultrasonic frequency of 40 kHz for 20 min. Then, 0.05 g of saccharin sodium (purity 98%) was added and ultrasonic dispersion was continued for 20 min to obtain a dispersion;

[0041] (2) The dispersion obtained in step (1) was magnetically stirred at 1000 rpm for 12 h at 25° C., and then centrifuged three times at 8000 rpm to collect the solid phase;

[0042] (3) After the solid phase obtained in step (2) is dried at 60° C. for 12 h, it is placed in a crucible, and the temperature is increased to 150° C. at a rate of 10° C. / min in a tubular furnace under a nitrogen atmosphere, and kept warm for 3 h to obtain a coated modified graphite negative electrode material.

[0043] The preparation method of the sulfide solid-state battery is carried out with reference to Example 1.

[0044] Example 3: Preparation of coated modified graphite negative electrode material and solid-state battery

[0045] A method for preparing a coated modified graphite negative electrode material comprises the following steps:

[0046] (1) 9.95 g of artificial graphite (particle size 15 μm) was weighed and placed in 60 mL of deionized water. Ultrasonic dispersion was performed at an ultrasonic frequency of 40 kHz for 20 min. Then, 0.05 g of saccharin sodium (purity 98%) was added and ultrasonic dispersion was continued for 20 min to obtain a dispersion;

[0047] (2) The dispersion obtained in step (1) was magnetically stirred at 1000 rpm for 12 h at 25° C., and then centrifuged three times at 8000 rpm to collect the solid phase;

[0048] (3) After the solid phase obtained in step (2) is dried at 60° C. for 12 h, it is placed in a crucible, and the temperature is increased to 300° C. at a rate of 10° C. / min in a tubular furnace under a nitrogen atmosphere, and kept warm for 3 h to obtain a coated modified graphite negative electrode material.

[0049] The preparation method of the sulfide solid-state battery is carried out with reference to Example 1.

[0050] Example 4: Preparation of coated modified graphite negative electrode material and solid-state battery

[0051] A method for preparing a coated modified graphite negative electrode material comprises the following steps:

[0052] (1) 9.9 g of artificial graphite (particle size 15 μm) was weighed and placed in 60 mL of deionized water, and ultrasonically dispersed at an ultrasonic frequency of 40 kHz for 20 min, and then 0.1 g of saccharin sodium (purity 98%) was added, and ultrasonic dispersion was continued for 20 min to obtain a dispersion;

[0053] (2) The dispersion obtained in step (1) was magnetically stirred at 1000 rpm for 12 h at 25° C., and then centrifuged three times at 8000 rpm to collect the solid phase;

[0054] (3) After the solid phase obtained in step (2) is dried at 60° C. for 12 h, it is placed in a crucible, and the temperature is increased to 200° C. at a rate of 10° C. / min in a tubular furnace under a nitrogen atmosphere, and kept warm for 3 h to obtain a coated modified graphite negative electrode material.

[0055] The preparation method of the sulfide solid-state battery is carried out with reference to Example 1.

[0056] Comparative Example 1 (the difference from Example 1 is that no saccharin sodium is added)

[0057] The method for preparing a graphite negative electrode material comprises the following steps:

[0058] (1) Weigh 9.95 g of artificial graphite (particle size 15 μm), place it in 60 mL of deionized water, and perform ultrasonic dispersion at an ultrasonic frequency of 40 kHz for 20 min to obtain a dispersion;

[0059] (2) The dispersion obtained in step (1) was magnetically stirred at 1000 rpm for 12 h at 25° C., and then centrifuged three times at 8000 rpm to collect the solid phase;

[0060] (3) After the solid phase obtained in step (2) is dried at 60° C. for 12 h, it is placed in a crucible, and the temperature is increased to 200° C. at a rate of 10° C. / min in a tubular furnace under a nitrogen atmosphere, and kept warm for 3 h to obtain a graphite negative electrode material.

[0061] The preparation method of the sulfide solid-state battery is carried out with reference to Example 1.

[0062] Comparative Example 2 (the difference from Example 1 is that direct mixing)

[0063] 9.95 g of artificial graphite (particle size 15 μm) and 0.05 g of sodium saccharin (purity 98%) were weighed and mixed evenly to obtain a graphite negative electrode material.

[0064] The preparation method of the sulfide solid-state battery is carried out with reference to Example 1.

[0065] Comparative Example 3 (the difference from Example 1 is that no sintering is performed)

[0066] The method for preparing a graphite negative electrode material comprises the following steps:

[0067] (1) 9.95 g of artificial graphite (particle size 15 μm) was weighed and placed in 60 mL of deionized water. Ultrasonic dispersion was performed at an ultrasonic frequency of 40 kHz for 20 min. Then, 0.05 g of saccharin sodium (purity 98%) was added and ultrasonic dispersion was continued for 20 min to obtain a dispersion;

[0068] (2) The dispersion obtained in step (1) was magnetically stirred at 1000 rpm for 12 h at 25° C., and then centrifuged three times at 8000 rpm to collect the solid phase;

[0069] (3) Drying the solid phase obtained in step (2) at 60° C. for 12 h to obtain a graphite negative electrode material.

[0070] The preparation method of the sulfide solid-state battery is carried out with reference to Example 1.

[0071] Comparative Example 4 (the difference from Example 1 is that sodium carboxymethyl cellulose is used to replace sodium saccharin)

[0072] The method for preparing a graphite negative electrode material comprises the following steps:

[0073] (1) 9.95 g of artificial graphite (particle size 15 μm) was weighed and placed in 60 mL of deionized water, and ultrasonically dispersed at an ultrasonic frequency of 40 kHz for 20 min, and then 0.05 g of sodium carboxymethyl cellulose was added, and ultrasonic dispersion was continued for 20 min to obtain a dispersion;

[0074] (2) The dispersion obtained in step (1) was magnetically stirred at 1000 rpm for 12 h at 25° C., and then centrifuged three times at 8000 rpm to collect the solid phase;

[0075] (3) After the solid phase obtained in step (2) is dried at 60° C. for 12 h, it is placed in a crucible, and the temperature is increased to 200° C. at a rate of 10° C. / min in a tubular furnace under a nitrogen atmosphere, and kept warm for 3 h to obtain a graphite negative electrode material.

[0076] The preparation method of the sulfide solid-state battery is carried out with reference to Example 1.

[0077] Comparative Example 5 (the difference from Example 1 is that saccharin is used to replace saccharin sodium)

[0078] The method for preparing a graphite negative electrode material comprises the following steps:

[0079] (1) 9.95 g of artificial graphite (particle size 15 μm) was weighed and placed in 60 mL of deionized water. Ultrasonic dispersion was performed at an ultrasonic frequency of 40 kHz for 20 min. Then, 0.05 g of saccharin (purity 98%) was added and ultrasonic dispersion was continued for 20 min to obtain a dispersion;

[0080] (2) The dispersion obtained in step (1) was magnetically stirred at 1000 rpm for 12 h at 25° C., and then centrifuged three times at 8000 rpm to collect the solid phase;

[0081] (3) After the solid phase obtained in step (2) is dried at 60° C. for 12 h, it is placed in a crucible, and the temperature is increased to 200° C. at a rate of 10° C. / min in a tubular furnace under a nitrogen atmosphere, and kept warm for 3 h to obtain a graphite negative electrode material.

[0082] The preparation method of the sulfide solid-state battery is carried out with reference to Example 1.

[0083] Solid-state battery performance testing

[0084] The prepared sulfide solid-state battery was charged and discharged for 3 cycles at 0.1C, 0.3C, 0.5C, 1C, and 2C under a test pressure of 5MPa and a charge and discharge range of -0.61 to 1.5V. The test results are shown in Tables 1 and Figure 4 , Figure 5 shown.

[0085] Table 1

[0086] project First-cycle Coulomb efficiency 2C discharge specific capacity (mAh / g) Example 1 88.68% 167 Example 2 86.49% 155 Example 3 86.24% 149 Example 4 85.75% 143 Comparative Example 1 83.11% 115 Comparative Example 2 84.70% 123 Comparative Example 3 85.63% 136 Comparative Example 4 83.27% 117 Comparative Example 5 85.01% 141

[0087] Figure 4 The first cycle charge and discharge curve of the sulfide solid-state battery obtained in Example 1 at a rate of 0.1C (the red line in the figure is charging, and the black line is discharging); Figure 5 This is a diagram of the discharge specific capacity of the sulfide solid-state battery obtained in Example 1 at different rates.

[0088] From Table 1 and Figure 4 , Figure 5 It can be seen that the sulfide solid-state battery obtained by using the coated modified graphite negative electrode material of Example 1 has a first-cycle coulomb efficiency and a discharge specific capacity at a 2C rate that are significantly higher than those of the sulfide solid-state batteries obtained by using the materials of Comparative Examples 1 to 5; the performance of the sulfide solid-state batteries obtained by using the coated modified graphite negative electrode materials of Examples 2 to 4 is also better than that of Comparative Examples 1 to 5; the experimental results of Example 1 and Comparative Example 5 show that under the same experimental conditions, saccharin sodium is more stable than saccharin, and the coating effect of saccharin sodium on graphite particles is better, and it can be seen from Example 1 and Comparative Example 4 that sodium element or sodium ion is not the main component for improving the performance of sulfide solid-state batteries; the experimental results of Examples 1 to 4 show that sulfide solid-state batteries assembled with materials prepared at different sintering temperatures and different coating contents show different performances, and the performance of Example 1 is better.

[0089] It can be seen that the use of the coated modified graphite negative electrode material of the present invention can achieve more stable and efficient and higher rate charge and discharge performance of the sulfide solid-state battery.

[0090] The preferred embodiments of the present invention are specifically described above, but the invention is not limited to the embodiments. Those skilled in the art may make various equivalent modifications or substitutions without violating the spirit of the invention. These equivalent modifications or substitutions are all included in the scope defined by the claims of this application.

Claims

1. A sulfide solid-state battery, characterized in that: The sulfide solid-state battery comprises a negative electrode sheet, the negative electrode sheet comprises a sulfide electrolyte and a coated modified graphite negative electrode material, the coated modified graphite negative electrode material comprises graphite and sodium saccharin, and the sodium saccharin is coated on at least a portion of the surface of the graphite; The mass of the sodium saccharin accounts for 0.1-1% of the mass of the coated modified graphite negative electrode material; The counter electrode of the sulfide solid-state battery is made of Li-In alloy; The method for preparing the coated modified graphite negative electrode material comprises the following steps: Mixing graphite, sodium saccharin and solvent, and performing ultrasonic dispersion to obtain a dispersion; Centrifuging the dispersion to collect the solid phase, and then drying and sintering the solid phase to obtain a coated modified graphite negative electrode material; The sintering process comprises: heating to 100-300° C. at a heating rate of 8-12° C. / min under an inert gas atmosphere, and keeping the temperature for 2-4 hours.

2. The sulfide solid-state battery according to claim 1, characterized in that: The graphite includes natural graphite and / or artificial graphite.

3. The sulfide solid-state battery according to claim 1, characterized in that: The particle size of the graphite is 5-30 μm.

4. The sulfide solid-state battery according to claim 1, characterized in that: The purity of the saccharin sodium is ≥98%.

5. The sulfide solid-state battery according to claim 1, characterized in that: The solvent includes at least one of water, ethanol and propanol.

6. The sulfide solid-state battery according to claim 1, characterized in that: The drying temperature is 50-80° C.; and / or the drying time is 6-12 hours.

Citation Information

Patent Citations

  • Anode active material for nonaqueous secondary battery and nonaqueous secondary battery using the same

    JP2011134572A